Benefits and limitations of prenatal screening for Prader–Willi syndrome. (12th October 2016) - Butler, Merlin G.
Abstract: This review summarizes the status of genetic laboratory testing in Prader–Willi syndrome (PWS) with different genetic subtypes, most often a paternally derived 15q11–q13 deletion and discusses benefits and limitations related to prenatal screening. Medical literature was searched for prenatal screening and genetic laboratory testing methods in use or under development and discussed in relationship to PWS. Genetic testing includes six established laboratory diagnostic approaches for PWS with direct application to prenatal screening. Ultrasonographic, obstetric and cytogenetic reports were summarized in relationship to the cause of PWS and identification of specific genetic subtypes including maternal disomy 15. Advances in genetic technology were described for diagnosing PWS specifically DNA methylation and high‐resolution chromosomal SNP microarrays as current tools for genetic screening and incorporating next generation DNA sequencing for noninvasive prenatal testing (NIPT) using cell‐free fetal DNA. Positive experiences are reported with NIPT for detection of numerical chromosomal problems (aneuploidies) but not for structural problems (microdeletions). These reports will be discussed along with future directions for genetic screening of PWS. In summary, this review describes and discusses the status of established and ongoing genetic testing options for PWS applicable in prenatal screening including NIPT and future directions for early diagnosis in PWS. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Genetic laboratory testing approaches for the diagnosis of Prader–Willi syndrome with different genetic subtypes do exist and other genetic testing options under development for application in prenatal screening. Early diagnosis of Prader–Willi syndrome leads to early treatment with improved quality of life, decreased comorbidities and reduced medical costs. What does this study add? A current review and summary of the literature relating to genetic testing in Prader–Willi syndrome with description of benefits and limitations for prenatal screening. Discussion of genetic testing approaches applied to prenatal screening with existing and emerging technologies leading to early diagnosis of Prader–Willi syndrome. Ultrasonographic features which may prompt suspicion of Prader–Willi syndrome.